Synthesis, Characterization and Thermal Behavior of Some Zn(II) Complexes with Ligands Having 1,3,4-Thiadiazole Moieties - Turan, Nevin; Sekerci, Memet (Wiley, 2010)
Some new zinc(II) complexes of the type [Zn(L-1)(2)(C2H5OH)(2)]center dot C2H5OH, [Zn(L-2)(2)Cl-2]center dot H2O, and [Zn-2(L-3)(2)(H2O)(4)Cl-4], where HL1 = N-[5'-amino-2, 2'-bis(1,3,4-thiadiazole)-5-yl]-2-hydroxybenzaldehyde imine, L-2 = N-(5-ethyl-1,3,4-thiadiazole-2-yl)terephthalaldehyde imine, and L-3 = N,N'-bis[5-(4-nitro phenyl)-1,3,4-thiadiazole-2-yl]terephthalaldehydedii-mine have been synthesized and characterized by IR, H-1 NMR spectra, elemental analyses, magnetic susceptibility, UV-vis. and thermogravimetry-differential thermal analysis (TGA-DTA). On the basis of electronic spectral studies, an octahedral environment around the Zn(II) ion has been suggested. H-1 NMR spectra of the metal complexes of ligands were found to be in agreement with the proposed stoichiometry. The presence of water molecules and ethanol in the Zn(II) complexes is also indicated by the thermal studies. (C) 20 10 Wiley Periodicals, Inc. Heteroatom Chem 21:14-23, 2010; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/hc.20572
Keywords: Schiff-Base Ligands; Transition-Metal-Complexes; Spectroscopic Characterization; Copper(Ii) Complexes; Cu(Ii); Co(Ii); Ni(Ii); Nickel(Ii); 2-Amino-5-Phenyl-1,3,4-Thiadiazole; Thiosemicarbazides